Special Issue on Recent Advances in Machine Learning and Applications - Wang, Chien-Chih (Processes, 2022)
Digital technologies for cyber-physical systems are rapidly advancing, and the ubiquity of the Internet of Things (IoT) has created significant challenges for academic, industrial, and service applications due to high dimensionality, noise contamination, incompleteness, inconsistency, and massive amounts of data [...]